Republic of Estonia : 2015 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Estonia's economic growth has slowed following the rebound from the deep recession in 2009. Although Estonia's economic and institutional fundamentals are among the strongest in the region, the economy is expected to expand by only a modest 1.6 percent in 2015. Growth is primarily driven by private consumption, which benefits from strong wage growth as labor market slack diminishes for demographic reasons. The economy should gather speed going forward. Growth is projected at 2.5 percent for 2016 and should average about 3 percent over the next few years.